Hypertension and its related factors among patients with type 2 diabetes mellitus - a multi-hospital study in Bangladesh - Hiba Alsaadon; Afsana Afroz; Afsana Karim; Samira Humaira Habib; Mohammed J. Alramadan; Baki Billah; Aishwarya Narendra Shetty (BMC, 2022)
Abstract Background Hypertension and type 2 diabetes are associated with each other, and their coexistence is linked to diabetes-related complications such as stroke, coronary artery disease, kidney disease, retinopathy and diabetic foot. This study aimed to determine the prevalence, awareness and control of hypertension and factors associated with hypertension among people with type 2 diabetes mellitus (T2DM) in Bangladesh. Methods A cross-sectional and retrospective study was conducted in 2017, and data from 1252 adults with T2DM were collected from six hospitals that specialise in diabetes care. These hospitals provide primary, secondary and tertiary healthcare and cover the rural and urban populations of Bangladesh. Cross-sectional data were collected from patients via face-to-face interviews, and retrospective data were collected from patients' past medical records (medical passport), locally known as the patients' guidebook or record book. The associations between hypertension and its related factors were examined using the bootstrapping method with multiple logistic regression to adjust for potential confounders. Results The mean age of participants was 55.14 (± 12.51) years. Hypertension was found to be present among 67.2% of participants, and 95.8% were aware that they had it. Of these, 79.5% attained the blood pressure control. The mean duration of diabetes was 10.86 (± 7.73) years. The variables that were found to be related to hypertension include an age of above 60 years, physical inactivity, being overweight or obese, a longer duration of diabetes and chronic kidney disease. Conclusion The prevalence of hypertension as well as its awareness and control were very high among people with known type 2 diabetes. As there is a strong relationship between hypertension and diabetes, patients with diabetes should have their blood pressure regularly monitored to prevent major diabetes-related complications.